Advanced Oxidation Processes (AOPs) in Wastewater Treatment - Deng, Yang; Zhao, Renzun (Current pollution reports, 2015)
Advanced oxidation processes (AOPs) were first proposed in the 1980s for drinking water treatment and later were widely studied for treatment of different wastewaters. During the AOP treatment of wastewater, hydroxyl radicals (OH·) or sulfate radicals (SO 4 ·− ) are generated in sufficient quantity to remove refractory organic matters, traceable organic contaminants, or certain inorganic pollutants, or to increase wastewater biodegradability as a pre-treatment prior to an ensuing biological treatment. In this paper, we review the fundamental mechanisms of radical generation in different AOPs and select landfill leachate and biologically treated municipal wastewater as model wastewaters to discuss wastewater treatment with different AOPs. Generally, the treatment efficiencies rely heavily upon the selected AOP type, physical and chemical properties of target pollutants, and operating conditions. It would be noted that other mechanisms, besides hydroxyl radical or sulfate radical-based oxidation, may occur during the AOP treatment and contribute to the reduction of target pollutants. Particularly, we summarize recent advances in the AOP treatment of landfill leachate, as well as advanced oxidation of effluent organic matters (EfOM) in biologically treated secondary effluent (BTSE) for water reuse.